Refreshment Kader Kesehatan Dalam Rangka Eliminasi Tuberkulosis - Saputra, Firman Firdauz; Kusumawardani, Eva Flourentina; Paradhiba, Meutia; Rimonda, Rubi; Siahaan, Perry Boy Chandra; Putra, Onetusfifsi; Fadillah, Mardi; Syam, Nasrianti; Harahap, Laila Apriani Hasanah; Raflythenu, Abdul Gani (Jurnal Abdi Mahosada, 2023)
Tuberculosis (TB) is still a significant health problem, with deaths reaching 1.3 million in 2016. Indonesia has a relatively high incidence of TB cases, reaching 391 cases per 100,000 population. One crucial element in handling tuberculosis cases is cooperating with Health Cadres in the community to solve TB problems. Cadres have an essential role in TB, starting from case detection, drug-taking supervision, and community empowerment. Hence, it is necessary to refresh their knowledge regularly and solve obstacles cadres face in the field. With this vital role, it is essential to consistently update the knowledge and skills of cadres in the community. The purpose of this service is to improve the knowledge and skills of cadres as well as to identify problems and constraints of cadres in society. Refreshment activities are carried out using lecture, and discussion techniques, with the media used being PowerPoint and cadre pocketbooks. Implementation evaluation is carried out using structural evaluation, processes, and results. The results of the evaluation conducted showed that the attendance of participants was >80%, and there was a significant increase in knowledge in participants from the results of the T-paired test that had been carried out. The refreshment activities carried out are always very important to maintain knowledge and skills and solve problems faced by cadres in the community and continually motivate cadres to do community empowerment well to create a healthy community and significantly eliminate tuberculosis cases..